Genital infection by Human papillomavirus (HPV) in women from Santa Catarina/Brazil - Fedrizzi, Edison Natal; Steffens, Sérgio Murilo; Menezes, Maria Elizabeth; Levi, José Eduardo (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Human papillomavirus (HPV) infection is the most common sexually transmitted infection in women. About 80% of sexually active women will have contact with this virus at some point in their lives. Most infections will be transient, but when the infection becomes persistent and associated with a high oncogenic risk of Human papillomavirus, there may be progression to cancer, especially cervical cancer. The best way to prevent Human papillomavirus infection is through the use of vaccines, which have been available to the public in Brazil since 2014. Objective: This study aimed to assess the most prevalent types of Human papillomavirus in the state of Santa Catarina, Brazil, and its mesoregions and if the majority of diagnosed types are contained in the Human papillomavirus vaccines currently available on the market. Methods: A total of 20,000 Human papillomavirus tests were evaluated for the diagnosis of genital Human papillomavirus infection in women from the state of Santa Catarina, Brazil. The prevalence of infection was evaluated according to age and the city of origin of the exams. Human papillomavirus detection was performed using molecular biology tests, such as hybrid capture (for diagnosis of the Human papillomavirus group, high or low oncogenic risk) and polymerase chain reaction (viral genotyping) techniques. Results: The diagnosis of Human papillomavirus infection was performed on women between 1 and 102 years of age. The age with the highest Human papillomavirus positivity, as expected, was 20–25 years (45.6%) and the lowest after 70 years (7.1%). The highest Human papillomavirus positivity of the exams was observed in the Serrana region of Santa Catarina state (58.9% of the exams). A high-oncogenic-risk Human papillomavirus was detected in 93% of positive samples and was the most frequent in all age groups. Mixed infection (high- and low-risk Human papillomavirus) was more prevalent in the 66–70 age group (29.3%) and in the Southern Region of Santa Catarina (26.4%). The most frequent genotypes in the state of Santa Catarina were non-16/18 high oncogenic risk Human papillomavirus (76.9% of positive cases). Human papillomavirus 16 was found in 17.1% of positive cases and Human papillomavirus 18 in 6.6%. Conclusion: The most prevalent types of Human papillomavirus in the state of Santa Catarina in the past 6 years are the non-16/18 high oncogenic risk Human papillomavirus types, which are viral types not covered by the current Human papillomavirus vaccines available in Brazil.